Pengaruh Motivasi dan Kompetensi Terhadap Kinerja Karyawan Bagian Produksi PT Widaya Inti Plasma Sidoarjo - Emy Nur Diana (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2018)
PT Widaya Inti Plasma is a company engaged in manufacturing sandals and shoes, and found problems that indicate low performance of production employee. The purpose of this study to determine 1). the effect of motivation on employee performance production section PT Widaya Inti Plasma Sidoarjo. 2). The effect of competence on employee performance production section PT Widaya Inti Plasma Sidoarjo. 3). The effect of motivation and competence on employee performance production section PT Widaya Inti Plasma Sidoarjo. This study using two type of data, namely secondary and primary. And this study is quantitative with number of sample 171 employee, with random sampling. This resultof this study shows (1) Motivation partially has a positive significant effect on employee performance, which t hitung 2,936 > t tabel 1,653 with 0,004 value of significance. (2) Competence has a positive significant effect on employee performance,which t hitung 6,842 > t tabel1,653 with 0,004 value of significance. Motivation and competence has a simultaneously has an effect on employees performance production section PT Widaya Inti Plasma with f hitung 31,431 > f tabel 3,05.